1996
DOI: 10.1097/00006231-199607000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution of 111In-labelled IgG and IgM in experimental infection

Abstract: SummaryBoth the protein used and the conjugation method are factors which may be relevant for targeting infection w ith n lIn-labelled proteins. In this study, human immunoglobulin G (IgG), conjugated to either DTPA or LiLo, and LiLo conjugated hum an immunoglobulin M (IgM) were evaluated. In rats with Staphylococcus aureus calf muscle infection, biodistribution was determined 6, 24 and 48 h after the injection of l1lIn-DTPA-IgG, ln In-LiLo-IgG or ln In-LiLo-IgM, Absolute abscess uptake of n lIn-LiLo-IgG w as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…111 In-IgG scintigraphy differentiated infectious from sterile inflammatory processes in 25 adult patients with complicated osteomyelitis or septic arthritis with a sensitivity of 90% and specificity of 95% (19). Oyen et al have reported that a recent bone trauma or fracture might be misleading in IgG scan interpretation (20)(21)(22). Unal et al, examining 20 cases of diabetic foot, reported a 100% versus 94% sensitivity and a 59% versus 100% specificity for 99m Tc-IgG and 99m Tcwhite blood cell labeling, respectively (18).…”
Section: Discussionmentioning
confidence: 99%
“…111 In-IgG scintigraphy differentiated infectious from sterile inflammatory processes in 25 adult patients with complicated osteomyelitis or septic arthritis with a sensitivity of 90% and specificity of 95% (19). Oyen et al have reported that a recent bone trauma or fracture might be misleading in IgG scan interpretation (20)(21)(22). Unal et al, examining 20 cases of diabetic foot, reported a 100% versus 94% sensitivity and a 59% versus 100% specificity for 99m Tc-IgG and 99m Tcwhite blood cell labeling, respectively (18).…”
Section: Discussionmentioning
confidence: 99%